Amyloidosis Cutis Dyschromica in a 16-Year-Old Filipino Girl: A Case Report - Fendi EJ R. Bautista; Marcia Marie S. Marte-Jimenez; Maria Jasmin J. Jamora (MDPI AG, 2022)
Amyloidosis cutis dyschromica is a rare variant of primary cutaneous amyloidosis characterized by hyper- and hypopigmented macules. In this paper, we reported a case of a 16-year-old Filipino girl with hyper- and hypopigmented to depigmented macules on the upper and lower extremities, which started when she was 9 years of age.